Inovasi Pemasaran dan Manajemen SDM Berkelanjutan dengan Pendekatan ABCD (Studi Kasus PT Berkah Tani Lestari Ponorogo) - Hamid Alwi Musarraf; Ahmad Kirom (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This service applies the ABCD (Asset-Based Community-driven Development) approach to develop marketing innovations and human resource management at PT Berkah Tani Lestari Ponorogo. The service was held from July 16 to August 28, 2025 at the Tani Lestari Blessing Garden, located in Njali Hamlet, Mrican Village, Jenangan District, Ponorogo Regency. ABCD is implemented by utilizing community assets in the form of agricultural land, local labor, farming experience, and existing marketing networks. These assets were identified and mobilized to design a marketing strategy for